Caracterização estrutural e propriedades antitumorais dos polissacarídeos extraídos da alga marinha vermelha Gracilaria caudata J Agardh. - Barros, Francisco Clark Nogueira (2011)
Seaweeds are considered an important source of bioactive molecules. In this work the red marine alga Gracilaria caudata was submitted to aqueous extraction of their polysaccharides and presented a recovery of 32.8%. The extracted polysaccharides of G. caudata (PGC) had 1% of sulfur atoms and a degree of sulfation of 0.13. The molar mass of PGC was determined by gel permeation chromatography and the molar mass detected was 2.5 x 105 g.mol-1. Chemical analysis made by spectroscopic methods such as Infrared and Nuclear Magnetic Resonance of PGC demonstrated to belong to the agar type galactan family, mainly constituted by alternating residues of β-D-galactose and 3,6-α-L-anhydrogalactose with the hydroxyl groups substituted by ester sulfate, methyl groups and pyruvic acid acetal. Seaweed polysaccharides have recently been shown to act as antitumor agents. The antitumor properties of the polysaccharides extracted from G. caudata (PGC) were investigated in vitro and in vivo. The cytotoxicity of PGC was evaluated in vitro by the methyl thiazolyl tetrazolium (MTT) assay. This assay demonstrated that PGC had IC50 values greater than 25 μg.mL-1 for all tested cells, being considered non-toxic. The in vivo antitumor activity of PGC against Sarcoma 180 cells transplanted in mice was evaluated and showed anticancer effect in both oral and intraperitoneal routes of administration. PGC significantly reduced tumor growth in 47.59 and 53.53% at the doses of 25 and 50 mg.kg-1 when administered intraperitoneally. The oral administration of 50 and 100 mg.kg-1 of PGC caused inhibition rates of 37.27 and 35.98%, respectively. Interestingly, PGC (25 mg.kg-1) enhanced the antitumor effect presented by 5-fluorouracil (10 mg.kg-1) from 37.22 to 70.74%. The histopathological analysis of liver and kidney showed that both organs were moderately affected by PGC treatment. Though, no significant changes in renal (urea) or liver (enzymatic activity of Alanine and Aspartate aminotransferase) parameters were observed. Results demonstrated that PGC administered by intraperitoneal route increased the relative spleen weight, induced a hyperplasia of lymphoid folicules, enhanced the neutrophil percentage and reverted the leucopeny induced by 5-FU, suggesting that the observed antitumor activity could be related to its immunomodulatory properties.